MODEL PENGEMBANGAN KOMPETENSI SUMBER DAYA INSANI (SDI) PADA BANK SYARIAH - Min Fadlillah, Alnisa -; Septyan, Krisno (Economic Faculty, Attahiriyah Islamic University, 2020)
The purpose of this study is to determine the development of human resource competencies in Islamic banking as well as a design model that provides an overview in formulating recommendations for developing SDI competencies due to problems that have occurred in Islamic banking in recent decades that caused by low level competency of human resources. This also driven by the lacking of availability human resources in the field of sharia. So this research is focused on understanding how the development of human resource competencies in accordance with Islamic sharia values. This study uses a qualitative method by interviews with informants consist of employees, former employees, and customers of Islamic banking. The results of this study also reveal that the Celestial Management theory by Riawan Amin which consists of three principles such as worship, wealth, and warefare that appropriate to be applied as a guide in sharia business values. Keywords : Model of competency development, Competence, Human Resources, Islamic banks